The role of cryoprecipitate in massively transfused patients: Results from the Trauma Quality Improvement Program database may change your mind. Issue 2 (August 2020) - Ditillo, Michael; Hanna, Kamil; Castanon, Lourdes; Zeeshan, Muhammad; Kulvatunyou, Narong; Tang, Andrew; Sakran, Joseph; Gries, Lynn; Joseph, Bellal
Abstract : BACKGROUND: Cryoprecipitate was developed for the treatment of inherited and acquired coagulopathies. The role of cryoprecipitate in hemorrhaging trauma patients is still speculative. The aim of our study was to assess the role of cryoprecipitate as an adjunct to transfusion in trauma patients. METHODS: We performed a 2-year (2015–2016) analysis of the American College of Surgeons-Trauma Quality Improvement Program data set and included all adult trauma patients who received 4 or greater packed red blood cells (pRBCs)/4 hours. Patients were stratified based on receipt of cryoprecipitate within the first 24 hours (cryoprecipitate vs. no-cryoprecipitate). Outcomes were blood products transfused, in-hospital complications, and mortality. Regression analyses were performed. RESULTS: A total of 19, 643 (cryoprecipitate, 4, 945; no-cryoprecipitate, 14, 698) were included. Mean age was 40 ± 22 years, median Injury Severity Score was 27 [18–40], and Glasgow Coma Scale score was 9 [3–14]. The overall complication rate was 45%, mortality was 47%, and 29% of the patients died in the first 24 hours. Patients in the cryoprecipitate group received a lower volume of plasma ( p < 0.01), and pRBCs ( p < 0.01). Additionally, patients who received cryoprecipitate had lower rates of 24-hour mortality ( p < 0.01) and in-hospital mortality ( p < 0.01). However, there was no difference between the two groups regarding complications ( p = 0.36) or volume of platelet transfused ( p = 0.22). On multivariate logistic regression, the use of cryoprecipitate was associated with decreased (odds ratio [OR], 0.78 [0.63–0.84]; p = 0.02), in-hospital mortality (OR, 0.79 [0.77–0.87]; p = 0.01), but had no association with in-hospital complications (OR, 1.48 [0.71–1.99]; p = 0.31). On linear regression analysis, the use of cryoprecipitate was not associated with 24-hour pRBCs (β = −0.12 [−0.28 to 0.27], p = 0.47), 24-hour plasma (β = −0.06 [−0.21 to 0.43], p = 0.29), and 24-hour platelets (β = −0.24 [−0.09 to 0.33], p = 0.17) transfusion requirements. CONCLUSION: The adjunctive use of cryoprecipitate in hemorrhaging trauma patients may reduce mortality without affecting in-hospital complications and transfusion requirements. Further studies are needed to better understand its potentially beneficial effects. LEVEL OF EVIDENCE: Therapeutic, level IV. Abstract : Supplemental digital content is available in the text.